The Prospects of Domestic Tourism in Post-Covid Nepal: Connecting the Missing Dots - Silwal, Ashma; Gonzales Garcia, Grizelda Noraine; Silwal, Amisha (Shanti Journal, 2022)
Nepal has experienced challenges in developing its international tourism business during Covid-19 and domestic tourism has not yet been considered a viable alternative to the allure of foreign travel in Nepal. There are no statistics on domestic tourism in Nepal. Worldwide, domestic tourism has been sought as an alternative to revive the tourism industry during a pandemic, and the Ministry of Tourism and Nepal Tourism Board is implementing strategies and plans to promote domestic tourism in Nepal. This study aims to investigate the potential of domestic tourism in Nepal from the perspective of domestic tourists. The study is qualitative in nature and has used an online survey from May to June 2020. Data has been analyzed thematically using SPSS, MS-Excel, and descriptive statistics. This study attempts to connect the dots by focusing on domestic tourism and tourist destinations in Nepal in accordance with respondents’ opinions. The findings reveal that the tourism industry can potentially be revitalized by domestic tourism. A high percentage of respondents indicated that the Covid lockdown has floored the tourism sector however, they are highly motivated to travel domestically rather than overseas despite the travel restrictions. To summarize, the potentiality of domestic tourism to strengthen the tourism industry should be further explored, and the absence of strategies and policies, travel restrictions, lack of provision of tourism infrastructure, and safety protocol are barriers to the flourishment of domestic tourism.